Pedagogical practice for science teaching during the COVID-19 pandemic in the view of Biological Sciences undergraduate students from a public Brazilian university (Research, Society and Development, 2022)
Due to the pandemic of COVID-19 and the need for social isolation, following World Health Organization guidelines, teaching activities began to be offered remotely in educational institutions. This study aimed to report the opinion of Biological Sciences undergraduate students from a public Brazilian university about the discipline Pedagogical Practice, developed in the remote format, during the COVID-19 pandemic. This is a qualitative-quantitative study, of the opinion poll type, with 17 students as public. The students' opinion was collected through an evaluative activity applied at the end of the course Pedagogical Practice online through Google Forms in the year 2021. Among some results, the students mentioned the decrease in the quality of the subject taught remotely, problems and difficulties in accessing the internet, with slow or unstable connections; the absence of face-to-face practical classes that makes it impossible to contact and socialize with teachers and classmates, and the overload and difficult concentration during this period.